Integrated and Comprehensive Action to Reduce and Control Dengue Hemorrhagic Fever: A Survey in Pekalongan City, Central Java - Nur Siyam (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: Dengue Hemorrhagic Fever (DHF) is an infectious disease that caused outbreaks in many areas in the Indonesia which led to high morbidity and mortality. Pekalongan City has the highest case fatality rate (CFR) of DHF among 35 cities and regencies in Central Java Province, which was 7.41% in 2008 and increased to 18.00% in 2009. The success of DHF control is largely determined by the cooperation of the public and decision-makers in various aspects and actions to be carried out. Therefore, it needs an integrated and comprehensive action to reduce and control DHF. In addition, to obtain the frequency distribution of DHF accurately and appropriately, an effective surveillance of hospital-early warning (KD-RS) and weekly outbreak (W2) reports are needed which requires timeliness and completeness as its report for early warning system of outbreak, so the morbidity and mortality due to DHF can be reduced.Objectives: This study is a survey with a descriptive approach to describe the level of implementation and regulation and activities conducted for dengue fever’s eradication program.Methods: Data was collected through observation, check list documentation and interviews. The subjects of this research were officers (head and staff) in the Division of Disease Prevention and Control-Environmental Health (P2P-PL) at Department of Health, Pekalongan City. Sampling technique is a total sampling. Data was analyzed and presented qualitatively.Results: The results showed that the key persons in population are an important individuals who responsible for community engagement in the village, institutions (schools and places of business, industries, offices), health centers, hospitals, families and individuals. Key interventions include organizing and managing resources. DHF prevention activities including preparation and implementation which cover many programs such as socialization, mobilization, selective larvacides, fogging prevention and focus, partnership with the non-goverment organisation (NGO), DHF suspect handling and monitoring and evaluation of activities through surveillance program.Conclusion: In conclusion, both reducing and controlling DHF in Pekalongan City was an integrated and comprehensive actions, involving key persons in populations and interventions.Keywords: integrated action, key persons, survey, DHF prevention